The reverse periculum in mora (Revista do Tribunal Regional Federal da 3ª Região, 2015)
This article analyzes the concept of periculum in mora in reverse by examining, first, the requirements for granting injunctive relief measures, namely, live and in the periculum iuris facie case. Then discusses the relevance of the merits of the request and the wide possibility of granting ex officio of injunctive relief in the form of an injunction, emphasizing the importance of identifying the substance of the application with iuris facie case and periculum in arrears. Subsequently, passes the specific study of periculum in live opposite, analyzing the relationship of this concept with the serious injury to the public order. Finally, appreciate the caution and contracautela.
Keywords: measures injuncitons; periculum in mora; iuris facie case; periculum lives in reverse or inverse; granting ex officio of injunctive relief; severe injury to the public order; countercaution